CONCUSSION IN THE EMERGENCY DEPARTMENT; UNCONSCIOUSLY INCOMPETENT?. Issue 12 (18th November 2016) - Phillips, TI; Guy, K; Tompkinson, A; Martin, R; Phillips, D; Sloan, N
Abstract : Objectives & Background: Sports related concussion is an increasingly common occurrence. Outside professional sport it is typically managed within Emergency Departments. The objective was to assess the level of knowledge and understanding of UK emergency medicine doctors of concussion; it's recognition, diagnosis and management. Methods: This was a cross-sectional observational study using self-report questionnaires. Questionnaires were distributed at regional EM conferences in July 2015 and January 2016. The questionnaire asked respondents to correctly identify signs and symptoms of concussion according to the 2012 Zurich consensus statement. It asked whether there were differences in the management of adult and paediatric concussion together with questions regarding RTP guidelines and use of potentially protective equipment. Results: 156 questionnaires were completed. Illegible answers, defaced or incorrectly completed questionnaires were discarded. 134 were included in the analysis. Training levels represented were: Consultant (10%), Specialist Registrar (12%), Staff Grade (5%), Core Trainee (34%), Foundation Trainee (20%), Emergency Nurse Practitioners (1.5%), Medical Students (16%). Answers to the symptomology questions were differentially weighted to produce an overall "Symptom Score" which was used for comparison. Consultants obtained the highest score (6.2). The least correct were Specialist Registrars (2.0). Diagnostic accuracy did not differ between secondary and tertiary centers (p=0.67). 80% of participants incorrectly identified headguards as being protective against concussion. 35.4% of respondents acknowledged a difference between adult and paediatric concussion. Conclusion: This small yet representative sample highlights a lack of knowledge in concussion in health professionals working in EDs in the UK. Despite the recent high profile cases in the media regarding the recognition and management of concussion, the frontline clinicians most likely to see concussive injuries have insufficient knowledge to diagnose and manage the condition effectively. There is an opportunity for Public health bodies, acute medical trusts and sports organisations to work collaboratively to provide education and resources for front line personnel that will increase awareness of concussion and improve care to patients presenting with concussive injuries.